REAL - Yearbook of Research in English and American Literature, Volume 31 (2015) Reading Practices - Fluck, Winfried; Leypoldt, Günter; Löffler, Philipp (REAL - Yearbook of Research in English and American Literature)
REAL invites contributions on the relationship between literature and cultural change. The study of culture has to face the difficulty of not being able to observe its object directly. Its only access is via cultural phenomena as observable products of human activity: artefacts, texts, rites, symbols, forms of conduct. If scholars wish to study cultural change, they need to do so by investigating the changing relationships among these phenomena, the changing connections between social structures, mentalities and the material dimension of texts, artefacts and other objects. While some scholars have rejected the concept of culture because of this indirectness, others - from Malinowski to Luhmann - have attempted to make it theoretically more precise and historically more saturated. Societies change as well as cultures, but they are not the same and they evolve at different speeds